Writing the past knowledge and literary production in archaeology - Lucas, Gavin 1965- (Routledge, 2019)
"How do archaeologists make knowledge? Debates in the latter half of the twentieth century revolved around broad, abstract philosophies and theories such as positivism and hermeneutics which have all but vanished today. By contrast, in recent years there has been a great deal of attention given to more concrete, practice-based studies, especially focusing on the coalface of archaeology, i.e. fieldwork. But where one was too abstract, the other has become too descriptive and commonly evades issues of epistemic judgement. This book remains within a practice-based approach but also tries to re-introduce a normative dimension to knowledge practices in archaeology - especially in relation to archaeological practice further down the 'assembly line': the production of published texts. For it is here that archaeological knowledge arguably becomes most stabilised and widely disseminated. By exploring the composition of texts in archaeology and the relation between their structural, performative characteristics and key epistemic virtues, this book aims to move debate in both knowledge and writing practices in a new direction. Although directed mainly at archaeologists, the argument offered in this book necessarily has relevance for all academic disciplines concerned with how knowledge production and textual composition intertwine"--